Prevalence of Impaired Fasting Glucose and Impaired Glucose Tolerance in Non-Diabetic Patients with Coronary Artery Disease - Nihar Ranjan Mohanty; Bhagyashree Panda (Golestan University Of Medical Sciences, 2022)
Background: Coronary artery disease (CAD) is one of the most common morbidities associated with diabetes mellitus. Impaired fasting glucose (IFG) and impaired glucose tolerance (IGT) are precursors to diabetes and major risk factors for atherosclerosis. The study aimed to evaluate the prevalence of IFG and IGT in nondiabetic patients with CAD. Methods: The study was performed on 100 non-diabetic patients with CAD and 50 healthy age- and sex-matched controls. Data were collected via detailed medical history taking, clinical examination, routine blood chemistry tests, fasting blood sugar test, 2-hour post-prandial blood sugar test, lipid profile, electrocardiogram, 2D-echocardiogram, and carotid Doppler. Results: Dyslipidemia was more prevalent among the patients. The mean carotid intima-media thickness was higher in the patients. Overall, IFG was found in 9 (15%) cases and IGT was found in 13 (22%) cases. The co-existence of IFG and IGT was detected in 3 (5%) cases. Abnormal glucose regulation was found in 42% of patients. Conclusion: The findings indicate the need for early screening and management of prediabetes for the prevention of further progression to diabetes.